Thrombosis in a young woman: It’s not what you think (Rheumatology Reports, 2011)
Hughes-Stovin syndrome is a very rare disease with fewer than 30 cases reported in the literature. This disease is characterized by the presence of pulmonary artery aneurysms in association with peripheral venous thrombosis. We report the case of a 29-year-old woman who initially presented with a deep venous thrombosis and pulmonary embolism with subsequent pulmonary artery aneurysms. The patient developed hemoptysis and was managed with arterial embolization, lobectomy, steroids and cyclophosphamide. Hughes Stovin syndrome should be considered in the diagnosis in young men and women who present with a peripheral venous thrombosis and pulmonary artery aneurysms. The majority of cases are reported in young men, unlike our case which occured in a young woman. Anticoagulation should be avoided due to the high risk of fatality in the setting of aneurysmal rupture.